Safety and feasibility of laparoscopic gastrectomy for remnant gastric cancer compared with open gastrectomy: Single-center experience. Issue 4 (29th January 2021) - Kitadani, Junya; Ojima, Toshiyasu; Nakamura, Masaki; Hayata, Keiji; Katsuda, Masahiro; Takeuchi, Akihiro; Tominaga, Shinta; Fukuda, Naoki; Motobayashi, Hideki; Nakai, Tomoki; Yamaue, Hiroki
Abstract : Abstract: The usefulness, safety and oncological validity of laparoscopic gastrectomy (LG) for remnant gastric cancer (RGC) have not been widely reported. A total of 38 patients who underwent gastrectomy for RGC were enrolled at Wakayama Medical University Hospital between April 2008 and December 2018. All consecutive patients were included in this retrospective study; the patients were divided into the open gastrectomy group and the laparoscopic group according to the sequential nature of their operation. Fifteen patients underwent open gastrectomy for RGC (OGR) between April 2008 and December 2013, and 23 patients underwent LG for RGC (LGR) after 2014. In the OGR group, all initial operations were performed by open surgery, whereas in the LGR group, 11 patients (47%) initially underwent laparoscopic surgery and 12 patients (53%) initially underwent open surgery ( P  = .002), 3 patients of which (25%) converted to open gastrectomy. There was no significant difference in the number of lymph node dissections or in operative time between the 2 groups, but blood loss was significantly lower in the LGR group than that in the OGR group ( P  = .002). Furthermore, although there was no difference between the 2 groups in C-reactive protein value on postoperative day 1, C-reactive protein value on postoperative day 3 was significantly lower in the LGR group than in the OGR group ( P  = .012). There were no differences in postoperative complications or long-term outcomes, including recurrence-free survival and overall survival. LGy is suitable in cases in which the initial surgery is performed by laparoscopic surgery. Even if the initial surgery is open surgery, it is oncologically equivalent to open gastrectomy and can be performed safely with less blood loss.